Stimulation of bone formation by monocyte-activator functionalized graphene oxide in vivo. Issue 41 (6th August 2019) - Bordoni, Valentina; Reina, Giacomo; Orecchioni, Marco; Furesi, Giulia; Thiele, Stefanie; Gardin, Chiara; Zavan, Barbara; Cuniberti, Gianaurelio; Bianco, Alberto; Rauner, Martina; Delogu, Lucia G.
Abstract : Graphene oxide complexed with calcium phosphate nanoparticles enhances bone regeneration through signalling between monocytes and mesenchymal stem cells. Abstract : Nanosystems are able to enhance bone regeneration, a complex process requiring the mutual interplay between immune and skeletal cells. Activated monocytes can communicate pro-osteogenic signals to mesenchymal stem cells and promote osteogenesis. Thus, the activation of monocytes is a promising strategy to improve bone regeneration. Nanomaterials specifically selected to provoke immune-mediated bone formation are still missing. As a proof of concept, we apply here the intrinsic immune-characteristics of graphene oxide (GO) with the well-recognized osteoinductive capacity of calcium phosphate (CaP) in a biocompatible nanomaterial called maGO-CaP (monocytes activator GO complexed with CaP). In the presence of monocytes, the alkaline phosphatase activity and the expression of osteogenic markers increased. Studying the mechanisms of action, we detected an up-regulation of Wnt and BMP signaling, two key osteogenic pathways. The role of the immune activation was evidenced by the over-production of oncostatin M, a pro-osteogenic factor produced by monocytes. Finally, we tested the pro-osteogenic effects of maGO-CaP in vivo . maGO-CaP injected into the tibia of mice enhanced local bone mass and the bone formation rate. Our study suggests that maGO-CaP can activate monocytes to enhance osteogenesis ex vivo and in vivo .